Serum titin/creatinine ratio as a biomarker for discriminating disease severity in Duchenne and Becker muscular dystrophies - Yoshinori Nambu; Kayo Osawa; Taku Shirakawa; Aiko Sunami; Shoko Sonehara; Ryosuke Bo; Kandai Nozu; Masafumi Matsuo; Hiroyuki Awano (Frontiers in Neurology)
IntroductionDuchenne/Becker muscular dystrophies (DMD/BMD) are inherited muscle diseases, collectively referred to as dystrophinopathy, which are characterized by progressive degeneration or loss. Although serum creatine kinase (CK) is a classical biomarker of DMD and BMD, it alone cannot clearly differentiate between severe DMD and milder BMD. Among potential biomarkers, the levels of the fragmented products of titin, a structural muscle protein, may directly reflect the degree of muscle loss in DMD and BMD. Therefore, this study measured the serum titin/creatinine (Cr) ratio and evaluated its discriminatory ability in patients with DMD and BMD.MethodsThe patients with dystrophinopathy and healthy controls were included in this study. Patients were classified by the reading frame rule (out-of-frame, DMD; in-frame, BMD). Exceptional cases in which in-frame variants presented with severe symptoms or out-of-frame variants presented with mild symptoms were considered clinically DMD or clinically BMD, respectively. Serum titin levels were measured using enzyme-linked immunosorbent assay. Serum Cr levels measured on the same day were used to calculate serum titin/Cr ratios.ResultsThe DMD, BMD, and control groups included 89 patients (85 DMD and four clinically DMD; aged 3–32 years), 21 patients (16 BMD and five clinically BMD; aged 6–33 years), and five participants (aged 7–12 years), respectively. Although serum CK levels did not differ significantly between DMD and BMD, the serum titin/Cr ratio in DMD was approximately 10 times higher than that in BMD group (p < 0.0001). Receiver operating characteristic curve analysis revealed that the ability of serum titin/Cr to distinguish DMD from BMD was superior to that of serum CK. Serum titin/Cr ratios in patients with DMD were higher than those with BMD across all age groups (3–10, 11–15, 16–20, and 21–33), but serum CK levels in patients with DMD were significantly higher than those with BMD only in the 11–15 and 21–33-year age groups.ConclusionUnlike serum CK, the serum titin/Cr ratio in patients with DMD was consistently higher than that in patients with BMD, regardless of age. Serum titin/Cr was shown to be a biomarker to discriminate clinical severity in patients with dystrophinopathy.